ОБГРУНТУВАННЯ ВИБОРУ РЕГУЛЯТОРА ШВИДКОСТІ ЕЛЕКТРОПРИВОДУ ОДНОЦИЛІНДРОВОГО ПОРШНЕВОГО КОМПРЕСОРА - Шуруб, Ю.В.; Попович, О.М.; Головань, І.В.; Бібік, О.В. (Інститут електродинаміки Національної академії наук України, 2023)
The peculiarities of the operation of closed systems of speed regulation of electric drives of single-cylinder piston compressors due to the presence of a non-linear dependence between the load torque and the angular movement of its rotor are considered. It is shown that the presence of an internal nonlinear connection, which forms a load torque, in a closed control systems can lead to subharmonic mechanical self-oscillations, which worsen the power and performance indicators of the electric drive. The use of static controllers is proposed to eliminate subharmonic self-oscillations and increase the efficiency of the electric drive. Ref. 10, fig. 6.